(untitled) (Studia Prawnicze / The Legal Studies, 1983)
The article deals with using computer systems of searching legal information. Having divided searching systems into those of direct and indirect searching the author states that it is impossible to use the former ones in this field. As far as the systems of indirect searching are concerned, special attention is paid to the description of structure and functioning of the statistical system. The article further deals with the structure of statistical thesaurus and the automatic expansion of searching instruction considering the advantages and disadvantages of certain variants; finally. The system LEX is shown in practice. At the end, an analysis of usefulness of statistical systems of searching legal information is carried out. In particular, it is stressed that those systems, owing to the fact that they automatically extend searching instruction introducing terms semantically similar to those applied by the user of the system, allow better searching than other systems. Some, mainly technical problems connected with introducing statistical systems of searching legal information, are also mentioned.